EFFECTIVENESS OF PRIVATE TUITION AND PARENTAL INVOLVEMENT AT THE PREPARATORY STAGE: INSIGHTS FROM INDIAN EDUCATION - Jha, Sanjeev Kumar (International Journal of Research -GRANTHAALAYAH, 2024)
This study investigates effectiveness of private tuition and parental involvement at the preparatory stage. This stage is critical as it establishes the foundation for academic path of the children. The decision between “private tuition” and “parental involvement” can significantly influence students’ educational experience, across the globe. This research aims to examine which of the approaches is more effective ‘private tuition’ or ‘parental involvement’ for the improvement of children’s academic achievement. The study used the survey method to collect background information and their school’s periodic examination scores as academic achievement. The study found that parental involvement has significantly more effective than private tuition in academic achievement of the students. It is crucial not only for a child’s academic development but also for the overall growth. The policy implication of the study is that in order to improve academic achievement and holistic development of children, it is recommended to promote parental involvement, especially during the preparatory stage.